2018
DOI: 10.1093/fampra/cmy120
|View full text |Cite
|
Sign up to set email alerts
|

Maternal work and exclusive breastfeeding in Mansoura, Egypt

Abstract: Background Working mothers face unique barriers to breastfeeding, despite the compelling evidence of its benefits. The aim of this study was to describe exclusive breastfeeding (EBF) rate of working mothers and associated factors. Methods Cross-sectional study was carried out in Mansoura District, Egypt from 1 July to 31 December 2017 among working mothers attending health care facilities for vaccinating their infants aged 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 20 publications
2
27
2
4
Order By: Relevance
“…Increased stress can impair lactogenesis and may lower oxytocin, thereby limiting milk letdown and output (Dewey, 2001;Stuebe, Grewen, & Meltzer-Brody, 2013). Further, food insecurity may compel mothers to seek employment outside the household or work for a greater proportion of the day, thereby disrupting normal feeding patterns and limiting the frequency and duration of feeding (Abou-ElWafa & El-Gilany, 2018;Nkrumah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Increased stress can impair lactogenesis and may lower oxytocin, thereby limiting milk letdown and output (Dewey, 2001;Stuebe, Grewen, & Meltzer-Brody, 2013). Further, food insecurity may compel mothers to seek employment outside the household or work for a greater proportion of the day, thereby disrupting normal feeding patterns and limiting the frequency and duration of feeding (Abou-ElWafa & El-Gilany, 2018;Nkrumah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, similar studies conducted in Colombia and other countries have explored multiple socioeconomic variables (e.g., work, government policies) that were not considered in this study (Abou-ElWafa & El-Gilany, 2019;Benjumea et al, 2011;Cabrera et al, 2004;Caleyachetty et al, 2013;Mateus, 2012;Muchacha & Mtetwa, 2014;Rodríguez-García & Acosta-Ramírez, 2008). Thus, future studies would need to address these limitations in order to provide a wider and holistic picture of the association between breastfeeding duration and preschoolers' eating behaviors in low-income Latino populations living in their country of origin.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Duration of breastfeeding is an important subject of cross-national debate given the importance of breastfeeding for child development and parenting practices (Biks et al, 2015;DiSantis et al, 2011;Ip et al, 2007;Li et al, 2010Li et al, , 2014Rodríguez et al, 2009;Savino et al, 2009;World Health Organization, 2012. Studies in different countries like India, Egypt and Zimbawe have revealed that social, economic and cultural factors may be potentially risky or protective for breastfeeding (Abou-ElWafa & El-Gilany, 2019;Borkhoff et al, 2018;Kumar et al, 2015;Miani et al, 2018;Reyes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2 Mısır'da çalışan kadınlarla yapılan çalışmada ev dışında tam zamanlı çalışmaya dönmenin emzirme süresinin azalması, doğum izni süresi artışının emzirme süresinin artmasıyla ilişkili olduğu belirlenmiştir. 33 Gana'da 369 profesyonel mesleğe sahip kadını kapsayan bir çalışmada emzirmenin sürdürülmesinde en önemli faktörün doğum izni olduğu belirtilmiştir. 20 Dagher ve ark.…”
Section: Discussionunclassified